2004
DOI: 10.1016/j.vetpar.2004.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development and serological antibody responses in sheep and rabbits experimentally infested with Psoroptes ovis and Psoroptes cuniculi

Abstract: Psoroptes ovis of sheep origin, and Psoroptes cuniculi of rabbit origin were used in experimental infestations. In experiment I, groups of four rabbits and four sheep were infested with 50-100 mites of each isolate on the skin of the back (skin infestation, SI) or in the external auditory canal (aural infestation, AI). In rabbits, SI and AI with P. cuniculi and AI with P. ovis induced in all animals typical ear lesions and pronounced antibody reactions to P. cuniculi antigens in ELISA. After SI of rabbits with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The control group underwent the same procedure, excluding the placement of mites [23]. To confirm that rabbits were infested, macroscopic lesions were identified with an otoscope.…”
Section: Methodsmentioning
confidence: 99%
“…The control group underwent the same procedure, excluding the placement of mites [23]. To confirm that rabbits were infested, macroscopic lesions were identified with an otoscope.…”
Section: Methodsmentioning
confidence: 99%
“…Boyce & Brown (1991) found only minor antigenic differences between mites from cattle, rabbits and bighorn sheep, and found mites from mule deer to be antigenically identical to those from bighorn sheep. Host transfer experiments of mites between rabbits and sheep have also shown that these mites are antigenically cross‐reactive (Siegfried et al ., 2004). A number of molecular studies have generated sequence data for the second internal transcribed spacer region (ITS‐2) of the ribosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence of rPc‐act showed high similarity to muscle actin genes in these species. Moreover, because of the distribution of the recombinant actin, which is mostly localized in the musculature, it can be classified as an isotype of muscle actin . Mounting evidence suggests that actin is involved in multiple processes during the life cycle of parasites and has critical importance in motility and endocytosis .…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the interval was extended to 14 days before the last injection. Two weeks later, the left ear of each rabbit was challenged with 25–50 vigorous adult P. cuniculi mites and wrapped with gauze for 48 h. Weight and lesion areas of each rabbit were recorded once per week since the start of infestation. The lesion areas were measured by otoscope and flexible ruler.…”
Section: Methodsmentioning
confidence: 99%